2001
DOI: 10.1159/000046832
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Features Control Temporal Plasticity in Auditory Cortex

Abstract: Cortical responses are adjusted and optimized throughout life to meet changing behavioral demands and to compensate for peripheral damage. The cholinergic nucleus basalis (NB) gates cortical plasticity and focuses learning on behaviorally meaningful stimuli. By systematically varying the acoustic parameters of the sound paired with NB activation, we have previously shown that tone frequency and amplitude modulation rate alter the topography and selectivity of frequency tuning in primary auditory cortex. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…In contrast, pairing the high-low-noise sequence with the same BF activation did not significantly alter either cortical topography or frequency bandwidth (data not shown). In addition, BF-sequence pairing led to shorter response latencies and increased population discharge synchrony that was not observed in any of the four earlier studies with simple tones or broadband stimuli (23)(24)(25)(26). The average time to peak (see Methods) was decreased by 3 ms after BF-sequence pairing (15.2 vs. 18.2 ms, P Ͻ 0.00001, Fig.…”
Section: Increased Response Synchronizationmentioning
confidence: 52%
See 1 more Smart Citation
“…In contrast, pairing the high-low-noise sequence with the same BF activation did not significantly alter either cortical topography or frequency bandwidth (data not shown). In addition, BF-sequence pairing led to shorter response latencies and increased population discharge synchrony that was not observed in any of the four earlier studies with simple tones or broadband stimuli (23)(24)(25)(26). The average time to peak (see Methods) was decreased by 3 ms after BF-sequence pairing (15.2 vs. 18.2 ms, P Ͻ 0.00001, Fig.…”
Section: Increased Response Synchronizationmentioning
confidence: 52%
“…Previous studies have shown that cortical receptive fields and temporal response properties can be substantially reorganized in an experience-dependent manner as a result of behavioral training or basal forebrain (BF) stimulation (20)(21)(22)(23)(24)(25)(26). The demonstration that cortical selectivity for simple stimuli remains plastic throughout adulthood has provided important insight into both the mechanisms and functional consequences of cortical plasticity.…”
mentioning
confidence: 99%
“…However, changes in spontaneous activity are not always observed in animals exposed to nucleus basalis stimulation. Pairing a single tone did not significantly alter spontaneous activity in any region of A1 (Kilgard et al, 2001b). In contrast, spontaneous activity was reduced when seven different tones distributed across the rat frequency range were randomly interleaved and paired with nucleus basalis stimulation (Kilgard et al, 2001b).…”
Section: Experiential Specificitymentioning
confidence: 69%
“…Pairing a single tone did not significantly alter spontaneous activity in any region of A1 (Kilgard et al, 2001b). In contrast, spontaneous activity was reduced when seven different tones distributed across the rat frequency range were randomly interleaved and paired with nucleus basalis stimulation (Kilgard et al, 2001b). Collectively these nucleus basalis induced plasticity studies suggest that the pattern of acoustic experience may also be important in determining the level of spontaneous activity.…”
Section: Experiential Specificitymentioning
confidence: 86%
See 1 more Smart Citation